137k views
1 vote
−4k + 6 − 2k= −3 (4k − 10)?

Sorry, I got perplexed about how I was doing this.

User Mahmudul
by
4.3k points

2 Answers

2 votes

Answer:

-3.5

Explanation:

-4k+ 6 - 2k= -3(-6k)

-4k+ 4k= 18k

-4k = 18k-4k

-4k = 14

-4k/-4 = 14/-4

K= -3.5

User Anth
by
4.6k points
2 votes

Answer:

k=4

Explanation:

−4k+6−2k=−3(4k−10)

−4k+6−2k=−3(4k−10)

−4k+6+−2k=(−3)(4k)+(−3)(−10)

−4k+6+−2k=−12k+30

(−4k+−2k)+(6)=−12k+30

−6k+6=−12k+30

−6k+6=−12k+30

−6k+6+12k=−12k+30+12k

6k+6=30

6k+6−6=30−6

6k=24

6k/6=24/6

k=4

(sorry if this was confusing)

User Dettorer
by
5.5k points